Measuring Financial Stability of Home-Based Women Workers (Living in Karachi) Through Micro-Credit Schemes - Umme-e-Hani; Manzoor, Dr. Asma; Shahid, Muhammad Saad Hassan; Manzoor, Dr. Seema (Journal of Peace, Development and Communication, 2023)
Women can seize many opportunities to fulfill their fundamental objectives by utilizing the micro-finance structure of empowerment. Their socio-economic structure and standard of living can change due to limited financial help or support from the public and private sectors. The most important aspect of this study is identifying the socio-economic problems that affect women and affectivity of applying for micro-credit loans through Micro-Credit Schemes. The key concept of this study is based on exploring how women’s work affects their family life and how they can gain economic empowerment and improve their lifestyle, knowledge, and understanding of the value of decision-making authority in this regard. This study’s main goal is to investigate the socio-economic issues faced by home-based women workers in Karachi, Pakistan. This research is based on quantitative research methodology to explore our aims, and goals, and to test the hypotheses. According to the facts, women struggle to support their families with little income, which connects the study’s background with the role of micro-financing schemes.